Evaluation of strategies for the prevention of mother-to-child transmission of HIV in Cameroon: a mixed qualitative and quantitative cross-sectional analysis from the Adamawa region of Cameroon - Bibiane Siaheu Kameni; Jobert Richie Nansseu; Jean Joel Bigna; Sandra Ayuk Tatah; Catherine Seyler (BMC, 2022)
Abstract Background To accelerate the fight against HIV/AIDS and eliminate the mother-to-child transmission (MTCT) of the virus, Cameroon has implemented and intensified several strategies despite which numerous children continue to be born infected with HIV. This study aimed to evaluate these strategies put in place for the prevention of MTCT (PMTCT) in Cameroon. Methods A qualitative and quantitative cross-sectional analysis was conducted in seven PMTCT care units situated in the Adamawa region of the country. The qualitative analysis included 16 individual interviews of key informants and observations of attitudes and practices being implemented in each unit. On the other hand, the quantitative analysis targeted 106 known HIV-positive breastfeeding women being followed-up at the unit. Results Task-shifting and sharing was effective, but majority of staffs had not received any specific training on PMTCT. Moreover, the integration of PMTCT within the maternal, neonatal and child health services remained ineffective, especially in health facilities of heavy workload. The coordination of PMTCT services was led by a well-designated focal person; however, his/her roles and responsibilities had not clearly been defined. Of the 106 women enrolled, 59.4% had a level of knowledge on PMTCT less than 80%. Similarly, their attitudes and practices towards PMTCT were inadequate or inaccurate in more than 60% of cases. Conclusion PMTCT strategies are globally well known and accepted by healthcare professionals. However, weaknesses have been figured out regarding service integration, task shifting and sharing, and coordination. In addition, beneficiaries' attitudes and practices are insufficient, and their level of knowledge does not guarantee to lessen the risk of MTCT of HIV.